Zakat Blockchain: A Descriptive Qualitative Approach - Lukman Hamdani (EkBis: Jurnal Ekonomi dan Bisnis, 2020)
Zakat as a tremendously effective tool for poverty minimization and social problems resolution, just like digital wallets can be used and optimized within the potential use of blockchain technology. Furthermore, zakat blockchain is one of the media instruments to cut the chain of zakat management and distribution, which is complex and requires much time. The synergy of amil zakat and muzakki in zakat blockchain is the right answer for welfare and time efficiency in distributing zakat to asnaf wherever they are. The methodology employed in this research was descriptive qualitative. This research was a descriptive study because it described or elucidated the combination of zakat and blockchain in Indonesia. The research approach used was qualitative. The objects of this research were zakat institutions in Indonesia. The subject of this research was the mechanism between muzakki and nadzhir in Indonesia This study’s results stated the importance of blockchain application and implementation for better zakat management